Desertification: an overview of processes and concepts, based on the application of orbital indices through remote sensing (Research, Society and Development, 2021)
Desertification has been an environmental problem all over the world, as a result of which there has been a growing interest in the last 50 years in relation to the impacts caused on society and on sustainability in general. The application of efficient techniques with low-cost tools is an alternative in identifying areas in the process of desertification. Among these techniques, remote sensing has gained prominence due to its robustness and reliable database. In this context, the objective of this review is to present the main factors that influence the desertification process in semiarid areas, as well as to understand the advances in studies on desertification through the use of remote sensing techniques. Currently, there are many methods used to identify desertified areas or areas in the process of desertification. The use of vegetation and soil indices are essential to identify these areas, as the absence of vegetation cover and soil condition can characterize a desertified environment. Remote sensing has helped to carry out studies for large areas and represents a promising alternative for the development of new methodologies that can be used to assess the risk of desertification. The findings of this review encourage the carrying out of studies and development of methodologies for studying desertified areas, especially in semiarid regions.